Design, synthesis, and structure activity relationship (SAR) studies of novel imidazo[1, 2-a] pyridine derivatives as Nek2 inhibitors. Issue 23 (1st December 2020) - Wang, Haili; Chen, Yunzhong; Gu, Xiaofan; Xi, Jianbei; Ren, Ziwei; Wang, Shuting; Duan, Yanhong; Li, Hongyu; Zhu, Tong; Du, Yijie; Zhang, Xiongwen; Ma, Mingliang
Graphical abstract: Highlights: A novel series of Nek2 inhibitors were designed and synthesized. Cell proliferation inhibitory was assessed on MGC-803 cells. 28e effectively inhibited the proliferation of MGC-803 cells. Abstract: Never in mitosis (NIMA) related kinase 2 (Nek2) is involved in multiple cellular processes such as cell cycle checkpoint regulation, cell division, DNA damage response and cell apoptosis. Nek2 has been reported to be overexpressed in various tumors and correlated with poor prognosis. Herein, a series of imidazo[1, 2- a ] pyridines Nek2 inhibitors were designed, synthesized, and their biological activities were investigated. Besides, structure activity relationship analysis of these compounds were performed in the MGC-803 cell. The screening results are promising, and compound 28e shows good proliferation inhibitory activity with an IC50 of 38 nM. The results would be helpful to design and develop more effective Nek2 inhibitors for the treatment of gastric cancer.